U is for undertow - Grafton, Sue. (New York : G.P. Putnam's Sons, 2009)
Hired by a preppy college dropout to discern the fate of a four-year-old girl who disappeared more than twenty years earlier, Kinsey Millhone investigates the young man's sketchy memories about a burial scene he believes he discovered at the age of six.
"A Marian Wood book."
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- California -- Fiction; Girls -- Crimes against -- Fiction; Mystery fiction